Measuring Automotive Company's Capabilities in Indonesia in Producing Profits Regarding Working Capital - Yuniningsih Yuniningsih; Veronika Nugraheni Sri Lestari; Nurmawati Nurmawati; Barid Nizarudin Wajdi (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2018)
The present research aims to determine company's ability to generate profit for capital or shareholders represented by proxy profitability and measured by return on equity (ROE) by taking into account working capital. The method of analysis used is multiple linear regressions with profitability as dependent variable and working capital as an independent variable in terms of cash cycle conversion variables, inventory turnover, and liquidity. The data used are secondary data from financial statements of automotive companies listed in Indonesia Stock Exchange (IDX) with the observation period of 2012-2016. The finding indicates that cash conversion cycle variable has a significant effect on profitability with negative direction yet does not support the hypothesis. Turnaround voucher variables support hypotheses which have a positive effect on profitability.  Liquidity variable has no significant effect on profitability. Limitation of this research is that working capital variable only based on 3 variables.  Implications created by the present study are that independent variables in this study have only contributed in explaining the dependent variable by 27.9%. Therefore, future study needs to be expanded with other variables of working capital or other variables. In addition, unit of analysis can be extended to companies other than automotive.